Pulsewidth control loop with a frequency detector for wide frequency range operation. Issue 4 (April 2015) - Kao, Shao-Ku; Cheng, Hsiang-Chi; You, Yong-De
Abstract A pulsewidth control loop (PWCL) with a frequency detector for wide frequency range operation is presented. The proposed PWCL is implemented with a duty cycle controlled circuit and frequency detector to correct the wide range frequency and duty cycle of the input clock. The duty cycle controlled circuit is able to modify the gain with different frequency and duty cycle ranges. The frequency and duty cycle of the input clock are detected by the frequency detector. The frequency detector is based on a ring oscillator and the input clock duty cycle and frequency are detected within two input clock cycles. The proposed circuit has been fabricated in a 0.35 μm CMOS technology. The proposed circuit generates the output clock of 50% duty cycle with the input range from 20% to 80% and frequency range 50–800 MHz. The measured duty cycle error is less than 1% within the frequency range from 50 MHz to 800 MHz.